A170: Neoplasms in Pediatric Patients with Rheumatic Diseases Exposed to Biologics—A Quarternary Centre's Experience. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Hasija, Rachana P; Silverman, Earl D.; Cho, Stephanie; Fung, Lillia; Benseler, Susanne M.; Cameron, Bonnie; Feldman, Brian M.; Laxer, Ronald M.; Levy, Deborah M.; Schneider, Rayfel; Spiegel, Lynn R.; Yeung, Rae SM; et al.
Abstract : Background/Purpose: Biologic therapies have revolutionized the management of rheumatic diseases of childhood. However, these medications are associated with adverse effects including the possible development of neoplasms. The aim of our study was to determine the rate as well as risk factors for the development of neoplasms in patients with JIA treated with biologics. Methods: We performed a retrospective review of the rheumatology biologic registry (RBR) at The Hospital for Sick Children (SickKids), Toronto, Canada, one of the largest quarternary pediatric referral centres in North America. Demographic and neoplastic data, clinical course and medication history were extracted from the RBR and clinical charts. Unless specified, data was expressed as median (IQR). The study was approved by the SickKids Ethics Review Board. Results: The cohort consisted of 357 patients with rheumatic diseases who were on one or more biologics between January 1997 and August 2013. Juvenile Idiopathic Arthritis (JIA) was the most common diagnosis [302/357 (84.5%)]. A total of 6/357 (1.68%) patients developed a neoplasm: 4 with JIA, 1 each with idiopathic uveitis and polyarteritis nodosa. (Refer to t87)1 Amongst patients with neoplasms, the median (IQR) age at rheumatic disease onset was 3.4 (1.7–7.3) years and the age of diagnosis of the neoplasm was 16.3 (15.3–17.9) years. All cancers were malignant except in patient 6 which was of a benign nature. On average, patients had exposure to 3 DMARDs (range 1–5), with methotrexate as the commonest DMARD used in 5/6 patients prior to diagnosis of the neoplasm. The time from the disease onset to initiation of DMARD was 3.9 (0.4–7.9) years. The time from the DMARD initiation and the diagnosis of a neoplasm was 10.1 (7.2–12.3) years. For methotrexate alone, the duration of use was 5.4 (3.9–6.1) years. All patients diagnosed with a neoplasm, had received both, DMARD(s) and biologic(s). 2 patients were on infliximab alone, 2 on etanercept alone and 2 on multiple biologics of which etanercept and infliximab were both used. The time between onset of a biologic and diagnosis of a neoplasm was 5.0 (3.6–7.7) years. Two patients (2 and 4) also received medications which are associated with the development of the neoplasms (cyclophosphamide or etoposide). Conclusion: Majority of neoplasms were of uncommon morphology and site as well as aggressive in nature. The neoplasms developed late after drug exposure with a median duration to diagnosis of neoplasm of 10.1 years on a DMARD and 5.5 years on a biologics. Whilst DMARDs and biologics are effective for the management of rheumatic diseases, patients with refractory disease requiring ongoing drug therapies should have malignancy/ neoplasm surveillance included as part of routine clinical care. Comparison of patients on biologics with and without neoplasms is in progress.